2011
DOI: 10.1111/j.1600-0412.2011.01201.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal understanding of commercial cord blood storage for their offspring – a survey among pregnant women in Hong Kong

Abstract: The results of this study revealed inadequate knowledge on UCB stem cell banking and its applications among most of our pregnant women. The government and clinicians should combine efforts to provide accurate information on utilization of UCB stem cells during antenatal care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Overall, papers exploring pregnant women’s and expectant parents’ knowledge and awareness of cord blood donation and banking, were conducted in 15 countries: North America and Canada [ 13 , 15 , 18 , 27 , 28 , 31 ], Europe and the United Kingdom [ 14 , 29 , 30 , 32 , 34 , 36 , 41 , 42 , 46 ], Australia [ 40 ], Asia and the Middle East [ 33 , 35 , 37 , 43 – 45 ], Africa [ 38 , 39 ] and one international study involving countries in Europe, Asia, Australasia, the Americas and Africa [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, papers exploring pregnant women’s and expectant parents’ knowledge and awareness of cord blood donation and banking, were conducted in 15 countries: North America and Canada [ 13 , 15 , 18 , 27 , 28 , 31 ], Europe and the United Kingdom [ 14 , 29 , 30 , 32 , 34 , 36 , 41 , 42 , 46 ], Australia [ 40 ], Asia and the Middle East [ 33 , 35 , 37 , 43 – 45 ], Africa [ 38 , 39 ] and one international study involving countries in Europe, Asia, Australasia, the Americas and Africa [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, as the figures above indicate, there has been a dramatic increase in private storage of cord blood. There exists also an evidence of poor public understanding of its medical utility . This evidence raises questions about the degree to which parental choices are informed and satisfy stated values and preferences .…”
mentioning
confidence: 99%
“…Unfortunately, poor knowledge about CB banking has been seen in many countries [9,14,15]. A previous study conducted in 5 European countries showed that 79% of the surveyed subjects had poor knowledge about CB banking [10].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have been conducted in several countries to learn about peoples' knowledge, understanding, preferences, and attitude toward CB banking. Unfortunately, most results have shown inadequate knowledge in the public, expecting mothers and even medical staff or health care providers to know about it [9][10][11][12][13][14][15]. Herein, we aimed to estimate the level of awareness of CB banking in the public of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%